PENGARUH KUALITAS PELAYANAN DAN FASILITAS TERHADAP KEPUASAN PENGUNJUNG DALAM PERSPEKTIF BISNIS ISLAM PADA OBJEK WISATA PANTAI GANDORIAH KOTA PARIAMAN - Mia Marsanda; Novera Martilova (Jurnal Ekonomi dan Bisnis, 2025)
The problem examined in this research is the influence of service quality and facilities on visitor satisfaction at the Gandoriah Beach tourist attraction. The type of data used is primary data obtained from respondents through distributing questionnaires. In taking samples using a purposive sampling method with a total of 100 respondents. The data analysis technique used is research instrument testing consisting of validity and reliability tests, classical assumption tests consisting of normality tests, autocorrelation tests, multicollinearity tests and heteroscedasticity tests, multiple  linear regression tests, coefficient of determination tests and hypothesis tests. Based on the results of research conducted using SPSS V 25, it shows that service quality has a significant effect on visitor satisfaction as evidenced by the results of tcount (14.570) ≥ ttable (1.98472) and a significant value (0.000) ≤ 0.05. Facilities have a significant effect on visitor satisfaction as evidenced by the results of tcount (3.434) ≥ ttable (1.98472) and a significant value (0.001) ≤ 0.05. The quality of services and facilities has a significant effect simultaneously on visitor satisfaction as evidenced by the results of the hypothesis test which shows Sig. (0.000) ≤ 0.05 and the fcount value (129.960) ≥ ftable (3.09). And the coefficient of determination test results obtained were 0.723 or 72.3%, so it can be concluded that the service and facility quality variables have a strong influence and contribute greatly to visitor satisfaction at the Gandoriah Beach tourist attraction. And the remaining 27.7% is influenced by other variables outside the variables included in this research.